Advaitic sādhanā : or The yoga of direct liberation : containing English translation of Māṇḍūkyopaniṣad and Ātmabodha - Cohen, Sulman Samuel, 1895- (Motilal Banarsidass, 1975)
On attaining self-knowledge through yoga.